Dos modos del artificio. La construcción poética de la historia en el pasaje de rómulo de las metamorfosis a la luz de los fastos - Martínez Astorino, Pablo (Athenaeum.)
In this paper, we analyse three kinds of appearance of history in the Romulus episode: 1. referential allusions to outstanding passages of the Romulus myth; 2. suppression of problematic references to his figure; 3. use of the Ennian intertext. Although points 1 and 2 have been understood as an example of historical or political correction, taking into account the importance of point 3 we will try to show that what prevails in the text is the representation of a poetic construction of history in terms of a device (this concept is duly explained): the three points, indeed, are intended to maintain or highlight the value of the central apotheosis theme, which, in the light of the ending, has a literary meaning. In Fasti, a work in which this device functions as a way of presenting the Romulus story according to his association with Augustus and his adaptation to times of peace, the image of Romulus fails to allude convincingly to Augustus because, in Ovid's times of peace, he no longer responds to the Romulean prototype of a new founder of the city, and the image of a pacifier Romulus, merely announced in Metamorphoses and Fasti, leads to Numa, the paradigm of the idea and a better foil to the "new" Augustus.